Review of Polymer Microfluidic Device Manufacturing Using Laser Technology - Salman, Safa N.; Rajab, Fatima H.; Issa, Ahmed A. (Al-Nahrain Journal for Engineering Sciences, 2024)
This paper provides a comprehensive overview of microfluidic device (MFD) manufacturing processes. The review starts with an introduction elucidating the significance and advantages of MFDs. Subsequently, a brief description of the materials employed in MFD fabrication is presented. The manufacturing process used to create MFDs is then thoroughly examined, with a focus on the application of laser technology.